Bery Engebretsen letter to Thomas H. Kent regarding fall bird sightings, November 30, 1997 - Engebretsen, Beryet al (1997)
Letter from Bery Engebretsen to Thomas H. Kent regarding fall bird sightings, November 30, 1997. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed/flatbed